Sino-German computational and applied mathematics - Braack, Malte; Gallistl, Dietmar; Hu, Jun; Kanschat, Guido; Xu, Xuejun (Computational methods in applied mathematics, 2021)
This short article serves as an epilog of the thirteen preceding papers in this special issue of CMAM. All contributions are authored by participants of the 7th Sino-German Workshop on Computational and Applied Mathematics at the Kiel University. The topics cover fourth-order problems, solvers and multilevel methods, a posteriori error control and adaptivity, and data science.